'Risky business': The future for female trekking guides in Nepal. (October 2019) - Hillman, Wendy
Over the years, much has been researched on male trekking guides, the trekking industry and male dominated and led tours. Research is lacking on female-only advancements made in this industry, and the risks that female guides experience daily. The research comes from face-to-face semi-structured interviews with 10 female trekking guides from Nepal. The interviews were undertaken with female guides employed by the '3 Sisters Adventure' trekking agency to ascertain the risks and safety issues for female trekking guides in the Himalayas. Findings suggest that female guides do indeed face risks and safety issues when guiding treks. More recently, female trekking guides have begun to carve their own niche within current Nepali tourism enterprises and into the future.